Synthesis and structure elucidation of hydrazones derived from N-(2,4-dimethylphenyl)-3-oxobutanamide - (:unkn) unknown (ARKAT USA INC, 2008)
Diazonium salts derived from amines 1 (sulfanilic acid, 4-nitroaniline, 4-aminosalicylic acid, sulfanilamide, sulfamethoxazole, sulfathiazole, sulfapyridine, sulfamerazine) were coupled with N-(2,4-dimethylphenyl)-3-oxobutanamide (2) resulting in the formation of hydrazones 3a-h.
Keywords: Azo coupling; hydrazones; BIOLOGICAL EVALUATION; COUPLING PRODUCTS; METABOLISM; COLORANTS; PIGMENTS